2018
DOI: 10.1103/physrevlett.121.052501
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Neutron Capture Cross Sections for Unstable Nuclei with Surrogate Reaction Data and Theory

Abstract: Obtaining reliable data for nuclear reactions on unstable isotopes remains an extremely important task and a formidable challenge. Neutron capture cross sections-crucial ingredients for models of astrophysical processes, national security applications, and simulations of nuclear energy generation-are particularly elusive, as both projectile and target in the reaction are unstable. We demonstrate a new method for determining cross sections for neutron capture on unstable isotopes, using ^{87}Y(n,γ) as a prototy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 61 publications
1
61
0
Order By: Relevance
“…This approach moves beyond the WE approximation which has been previously shown, and here confirmed, to be inadequate for neutron capture [22,26,27]. We show that a robust model of the formation of the CN [13,14] and proper treatment of its decay [30,31] within the framework of the SRM [11,30,31] is necessary to extract from (d, pγ) data a capture cross section that agrees with the directly-measured (n, γ) cross section. We note that the kinematics of the (d, p) reaction are ideal for measurements with short-lived beams in inverse kinematics.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…This approach moves beyond the WE approximation which has been previously shown, and here confirmed, to be inadequate for neutron capture [22,26,27]. We show that a robust model of the formation of the CN [13,14] and proper treatment of its decay [30,31] within the framework of the SRM [11,30,31] is necessary to extract from (d, pγ) data a capture cross section that agrees with the directly-measured (n, γ) cross section. We note that the kinematics of the (d, p) reaction are ideal for measurements with short-lived beams in inverse kinematics.…”
supporting
confidence: 54%
“…Specifically, nuclear level densities (NLD) and γ-ray strength functions (γSF) determine whether the CN decays primarily by neutron or γ-ray emission. A newly-developed method by Escher and colleagues [30,31] constrains the parameters in the decay models via Bayesian fits to the experimentally-measured surrogate coincidence probabilities. The constrained parameters are subsequently used to calculate the cross section for the (n, γ) reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Escher et al [268] accomplished the surrogate method without exploiting the Weisskopf-Ewing approximation. By exploring a large parameter space, they demonstrated that a set of model parameters for the level density and γ-ray strength function could describe the experimental γ-decay probabilities P γ (E n , J, π).…”
Section: Surrogate Reaction Methods For Statistical Capturementioning
confidence: 99%
“…For such calculations, there are several models and parameter sets that can be chosen from literature, and typically the spread in calculated cross sections may vary within factors of ≈ 5 − 10. To quantitatively determine this spread, Escher et al [268] have tested the sensitivity of the calculations using several input options [113,110,271,272,273]. The resulting systematic-error band is shown in panel (f) of Fig.…”
Section: Surrogate Reaction Methods For Statistical Capturementioning
confidence: 99%